PROFIL DES LIPIDES SERIQUES DES SUJETS ADULTES BENINOIS CONSOMMATEURS HABITUELS DE TABAC - Gomina, Moutawakilou; Ngobi, Gado Yarou; Akpona, Simon Ayélèroun (European Scientific Journal, ESJ, 2013)
Introduction: Tobacco consumption alters several biological parameters. This study aimed to describe the serum lipids profile of Benin adult subjects who are usual tobacco smokers, snuffers and chewers. Methods: We performed a cross-sectional and analytical descriptive study from April 1st to August 30th, 2012 in Benin adult subjects who are usual tobacco consumers (60 smokers, 60 chewers, 60 snuffers) and in 60 subjects who are not tobacco consumers. The following serum lipid parameters were measured: Total cholesterolemia (TC), HDL cholesterolemia (HDL- C), triglyceride (TG) levels, LDL cholesterolemia (LDL- C), VLDL cholesterolemia (VLDL- C) and atherogenic index (AI). The analysis of variance (ANOVA) improved by Student’s t test allowed to compare averages between the different study groups. Simple or multiple associations between the different variables were tested on 5% threshold by means of Person’s chi2 and Fisher’s F comparison tests. Linear regression was used to determine the different correlations. Results: TC, HDL- C and AI averages were significantly higher in chewers than in snuffers (p ≤ 0.02). CT and HDL- C averages were significantly higher in chewers than in smokers (p ≤ 0.002) whereas TG and VLDL- C had significantly lower average values (p < 0.02). TG, LDL- C and VLDL- C averages were significantly higher in smokers than in snuffers (p < 0.05). TG, VLDL- C and AI averages were significantly higher in snuffers than in non consumers (p < 0.03) while non-consumers showed an HDL- C average that was significantly higher (p = 0.001). TC, HDL-C, TG and VLDL- C were significantly higher in chewers than in non consumers (p < 0.02). TG, VLDL-C and AI were significantly higher in smokers than in non-consumers (p < 0.006). There were average correlations for TG and VLDL- C (r = +0.203 and +0.207 respectively) in snuffers and for HDL- C, LDL- C and AI (r = +0.229, +0.248 and +0.242 respectively) in smokers with the number of years of tobacco consumption. Only smokers presented an average correlation with daily quantity of tobacco consumed (r = +0.257) as for TC. Conclusion: Tobacco modifies serum lipid values, regardless of its mode of consumption. Subsequently, it fosters the development of atheromatosis.